The Successful Implementationof the Independent Learning - Independent Campus: The Study onThe Program of Right to Learn for Three Semesters Outside the Study Program - Anggarwati, Ratna Dwi (Universitas Muhammadiyah Sidoarjo, 2022)
A new stage of education in Indonesia began when President Joko Widodo appointed NadiemMakarim as Minister of Education, Culture, Research, and Technology of the Republic of Indonesia. He issued the policy called Merdeka BelajarKampus Merdeka (MBKM) meaning “Freedom to learn, Independent Campus or the Independent Learning- Independent Campus”. This research analyzed the successful implementation of an MBKM Program in the Communication Study Program at UniversitasMuhammadiyah Sidoarjo. It used the approach of two policy implementation theories from Michael Hill & Peter L Hupe and Hudson, Hunter & Peckham. They have eight aspects of excellence in their analysis. The research method approach in this analysis used descriptive qualitative data collection using several data collection techniques such as interviews, observation, and documentation studies. The results of this researchshowed that the Communication Studies Program at Universitas Muhammadiyah Sidoarjo has implemented the success from an administrative and practical perspective. From the eight aspects of the analysis of the successful implementation of the policy, several aspects that supported this success consisted of the policy environment, implementation preparation, and implementation support.